The hawk and the dove Paul Nitze, George Kennan, and the history of the Cold War - Thompson, Nicholas (Henry Holt and Company, 2009)
Only two Americans held positions of great influence throughout the Cold War; ironically, they were the chief advocates for the opposing strategies in that harrowing conflict. Both came to power during World War II, reached their professional peaks during the Cold War's most frightening moments, and fought epic political battles that spanned decades. Yet despite their very different views, Paul Nitze and George Kennan remained good friends all their lives. Nitze--the hawk--believed that the best way to avoid a nuclear clash was to prepare to win one. More than any other American, he was responsible for the arms race. Kennan--the dove--persuasively argued that we should contain the Soviet Union while waiting for it to collapse from within. In following these two rivals and friends from the beginning of the Cold War to its end, Nicholas Thompson tells the story of our nation during the most dangerous half century in history.--From publisher description.
Keywords: Nitze, Paul H; Kennan, George F -- (George Frost) -- 1904-2005; Kennan, George Frost -- 1904-2005; Nitze, Paul H. -- 1907-2004; Geschichte 1900-2000; Außenpolitik; Geschichte; Cold War; National security -- United States -- History -- 20th century; Anti-communist movements -- United States -- History -- 20th century; Ambassadors -- United States -- Biography; Ost-West-Konflikt; USA; United States -- Foreign relations -- 1945-1989; United States -- Officials and employees -- Biography; Biografie